2019
DOI: 10.1128/jvi.01808-18
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus E6/E7 and Long Noncoding RNA TMPOP2 Mutually Upregulated Gene Expression in Cervical Cancer Cells

Abstract: TMPOP2 was previously suggested to be an oncogenic long noncoding RNA which is excessively expressed in cervical cancer cells and inhibits E-cadherin gene expression by recruiting transcription repressor EZH2 to the gene promoter. So far, the function and regulation of TMPOP2 in cervical cancer remain largely unknown. Herein, we found that TMPOP2 expression was correlated with human papillomavirus 16/18 (HPV16/18) E6 and E7 in cervical cancer cell lines CaSki and HeLa. Tumor suppressor p53, which is targeted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 38 publications
(42 reference statements)
1
39
0
Order By: Relevance
“…Our own experiments revealed increased EBIC expression in HPV16 E6/E7 expressing HFKs as compared to control HFKs [93] ( Figure 2B). Consistent with these results, a recent study suggested that EBIC expression was driven by E6/E7 expression, and largely due to E6 mediated TP53 degradation [39]. Interestingly, EBIC was reported to cause increased expression of HPV E6/E7 through a mechanism that involves sponging of miR-375 and miR-139, which have been previously reported to target HPV E6/E7 [112,113] (Figure 5).…”
Section: Ebic (Tmpop2)supporting
confidence: 80%
See 1 more Smart Citation
“…Our own experiments revealed increased EBIC expression in HPV16 E6/E7 expressing HFKs as compared to control HFKs [93] ( Figure 2B). Consistent with these results, a recent study suggested that EBIC expression was driven by E6/E7 expression, and largely due to E6 mediated TP53 degradation [39]. Interestingly, EBIC was reported to cause increased expression of HPV E6/E7 through a mechanism that involves sponging of miR-375 and miR-139, which have been previously reported to target HPV E6/E7 [112,113] (Figure 5).…”
Section: Ebic (Tmpop2)supporting
confidence: 80%
“…Interestingly, EBIC was reported to cause increased expression of HPV E6/E7 through a mechanism that involves sponging of miR-375 and miR-139, which have been previously reported to target HPV E6/E7 [112,113] (Figure 5). EBIC depletion in the HPV18 positive HeLa cervical carcinoma line inhibited proliferation by affecting the expression of cell cycle genes such as p21 CIP1 (CDKN1A), cyclin E, and CDK2 [39].…”
Section: Ebic (Tmpop2)mentioning
confidence: 99%
“…The specific molecular mechanisms between the persistent high-risk HPV infection and the pathological process of CC are still controversial ( 5 ). Increasing evidence has shown that the abnormal expression of multiple genes are involved in the pathogenesis of CC ( 6 ). As tumorigenesis is a complex pathological process involving various genetic and epigenetic events, such as the inactivation of suppressor genes and/or the overexpression of oncogenes ( 7 ), the identification of dysregulated genes in cancer-associated pathways may highlight the molecular mechanisms underlying tumorigenesis, assisting in the development of novel strategies for treatment of CC.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 He et al, reported that HPV16 E6/E7 and the lncRNA-TMPOP2 form a positive feedback loop to mutually strengthen oncogene expression and repress tumor repressor expression in CC. 16 A recent study identified lncRNAs expression alterations after HPV16 E6 overexpression using RNA sequencing. 17 They found that 151 lncRNAs are upregulated and 100 lncRNAs are downregulated when HPV16 E6 was expressed in keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…E7 and lncRNAs (eg, TMPOP2) can form a positive feedback loop to mutually enhance oncogene expression and inhibit tumor repressor expression. 16 A large number of lncRNAs are abnormally expressed due to HPV16 E6 overexpression. 17 Additionally, lncRNA can function as ceRNA to regulate mRNA expression through sponging miRNAs.…”
mentioning
confidence: 99%